Identifikasi Kandungan Boraks pada Tahu Putih di Pasar Wage Banjarharjo Brebes - Umi Khusna; Laila Kusumaningrum; Dwi Yuliani; Anwar Jaman (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Tofu is a daily staple food that is often consumed by Indonesian people because it is affordable and contains high protein. Poisoning with preservatives (borax) can occur through food or snacks, one of which is tofu. This research aims to analyze the borax content in white tofu food at the Wage Banjarharjo Brebes Market. This research method is laboratory observation. The sample used was white tofu which was bought and sold at the Banjarharjo wage market, which was taken randomly from 14 traders. The method used for the qualitative test of borax is using the flame test and the quantitative test is the acid-base titration test. Analysis of research results was carried out descriptively. Based on the results of qualitative research using the flame test, it shows that tofu contained positive borax in samples from traders B, H and L. Meanwhile, tofu that did not contain borax or was negative was A, C, D, E, F, G, I, J, K, M, and N. In addition, the results of research using a quantitative method using the acid base titration method showed that the volume of borax with levels in trader B was 1.1% (w/w), in trader H 2.9% (w/w) and in the sample trader L 2.5 % (w/w).